2021
DOI: 10.1080/21655979.2021.1915727
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-9 restrains the sharp increase and boost apoptosis of human acute myeloid leukemia cells by adjusting the Hippo/YAP signaling pathway

Abstract: MicroRNAs (miRNAs) play a very important role in the development of acute myeloid leukemia (AML). This study focuses on the effects of miR-9 on the regulation of AML cells and their related signaling pathways. We found that the expression of miR-9 was significantly decreased in four AML cell lines (THP-1, HL-60, TF-1 and KG-1) compared with the human normal bone marrow cells (HS-5). Moreover, miR-9 overexpression inhibited HL-60 cell proliferation ability, and promoted apoptosis. However, interfering with miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…It was reported that pyruvate kinase M1/2 (PKM) controlled the proteins level of cell apoptosis and proliferation-related genes by activating Hippo signaling pathway ( Luo et al, 2021 ). MiR-9 was found to promote apoptosis in human acute myeloid leukemia cells by regulating the Hippo-YAP signaling pathway ( Wang et al, 2021 ). P62/SQSTM1 co-located with the hippocampal signaling modulator Dachs and inactivated the Hippo signaling pathway, leading to excessive non-cellular proliferation of stem cells ( Nagai et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that pyruvate kinase M1/2 (PKM) controlled the proteins level of cell apoptosis and proliferation-related genes by activating Hippo signaling pathway ( Luo et al, 2021 ). MiR-9 was found to promote apoptosis in human acute myeloid leukemia cells by regulating the Hippo-YAP signaling pathway ( Wang et al, 2021 ). P62/SQSTM1 co-located with the hippocampal signaling modulator Dachs and inactivated the Hippo signaling pathway, leading to excessive non-cellular proliferation of stem cells ( Nagai et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have similarly demonstrated that the MAPK12 gene was upregulated at MDS diagnosis and downregulated in normal BM colonies after four cycles of treatment (25). The Hippo signaling pathway interacts with other growth control and cell proliferation pathways such as PI3-AKT, TGF-b, RAS-MAP kinase, JAK/ STAT, Notch, and Wnt signaling through YAP (Yes-associated protein) activation (28), and the downregulation of miR-9 and miR-550-1 is postulated to contribute to AML pathogenesis through inhibition of their tumor suppressor functions on the Hippo and YAP signaling pathways (29,30). In CML, the downregulation of miR-181a resulted in the decreased activation of YAP and restored sensitivity to the tyrosine kinase inhibitor imatinib (31).…”
Section: Discussionmentioning
confidence: 99%
“…The Hippo-YAP signalling pathway is an evolutionally conserved pathway that is associated with tumour development (50)(51)(52)(53)(54). YAP is a downstream effector of this pathway (55).…”
Section: Discussionmentioning
confidence: 99%